The regression detectability index RDI for mammography images of breast phantoms with calcification-like objects and anatomical background. (18th November 2021) - Anton, M; Reginatto, M; Elster, C; Mäder, U; Schopphoven, S; Sechopoulos, I; van Engen, R
Abstract: Currently, quality assurance measurements in mammography are performed on unprocessed images. For diagnosis, however, radiologists are provided with processed images. This image processing is optimised for images of human anatomy and therefore does not always perform satisfactorily with technical phantoms. To overcome this problem, it may be possible to use anthropomorphic phantoms reflecting the anatomic structure of the human breast in place of technical phantoms when carrying out task-specific quality assessment using model observers. However, the use of model observers is hampered by the fact that a large number of images needs to be acquired. A recently published novel observer called the regression detectability index (RDI) needs significantly fewer images, but requires the background of the images to be flat. Therefore, to be able to apply the RDI to images of anthropomorphic phantoms, the anatomic background needs to be removed. For this, a procedure in which the anatomical structures are fitted by thin plate spline (TPS) interpolation has been developed. When the object to be detected is small, such as a calcification-like lesion, it is shown that the anatomic background can be removed successfully by subtracting the TPS interpolation, which makes the background-free image accessible to the RDI. We have compared the detectability obtained by the RDI with TPS background subtraction to results of the channelized Hotelling observer (CHO) and human observers. With the RDI, results for the detectability d ′ can be obtained using 75% fewer images compared to the CHO, while the same uncertainty of d ′ is achieved. Furthermore, the correlation of d ′ (RDI) with the results of human observers is at least as good as that of d ′ (CHO) with human observers.